Private Investment in Developing Countries : An Empirical Analysis. (IMF Working Papers; Working Paper ;, 1990)
This paper analyzes the effects of several policy and other macro-economic variables on the ratio of private investment to GDP in developing countries. Using data for a sample of 23 developing countries over the period 1975-87, the econometric evidence indicates that the rate of private investment is positively related to the real growth rate of GDP, public sector investment, and to a lesser extent the level of per capita GDP, while it is negatively related to domestic inflation, the debt service ratio, the debt-to-GDP ratio, and high real interest rates. There is also some indication that all but the last of these variables had a greater impact before the onset of the debt crisis in 1982, while the debt-to-GDP ratio (a measure of a country's debt overhang) has become more important since then.